2020
DOI: 10.1136/fmch-2019-000247
|View full text |Cite
|
Sign up to set email alerts
|

Provision of primary care by specialist physicians: a systematic review

Abstract: Patients with stable chronic diseases such as diabetes and hypertension can be safely managed at the primary care level. Yet many such patients continue to follow-up with specialists at a higher expense with no added benefit. We introduce a new term to describe this phenomenon: scope inversion, defined as the provision of primary care by specialist physicians. We aimed to quantify the extent of scope inversion by conducting a systematic review. MEDLINE and five other databases were searched using the keywords … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“… 6 , 7 Inappropriate referral and a lack of appropriate differential diagnoses are risk factors of diagnostic errors. 2 , 8 Some studies reported that specialists see more patients with stable chronic diseases than generalists 9–11 in daily practice; therefore, when they encounter patients with undiagnosed new health problems that are irrelevant to their specialty domain, more unnecessary cross-referrals to other specialists and diagnostic tests occur, 9 , 11 , 12 which result in diagnostic errors, patient harm, and consumption of healthcare resources. 2 , 5 Indeed, a previous study showed that approximately 10% of infectious disease consultations from other specialty departments associated with fever or inflammation of undetermined origin were due to non-infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 Inappropriate referral and a lack of appropriate differential diagnoses are risk factors of diagnostic errors. 2 , 8 Some studies reported that specialists see more patients with stable chronic diseases than generalists 9–11 in daily practice; therefore, when they encounter patients with undiagnosed new health problems that are irrelevant to their specialty domain, more unnecessary cross-referrals to other specialists and diagnostic tests occur, 9 , 11 , 12 which result in diagnostic errors, patient harm, and consumption of healthcare resources. 2 , 5 Indeed, a previous study showed that approximately 10% of infectious disease consultations from other specialty departments associated with fever or inflammation of undetermined origin were due to non-infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Key performance indicators have to be carefully mapped to the strategic, long-term aims of the institutions. Systems thinking starts with a people first attitude and leads to enabling systems that are respected and upheld 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Coronary artery disease (CAD) is considered a complex disease, and the morbidity, mortality, disability, and recurrence rates are high [1,2]. CAD became one of the most common causes of death in the Chinese population in 2015 [3,4].…”
Section: Introductionmentioning
confidence: 99%